Biotechnology in animal feeds and animal feeding - Wallace, R. John.; Chesson, A. (VCH, 1995)
With the dramatically rising sophistication of biological methods and products and the increasing use of recombinant DNA technology, now is an apt time to review the status of biotechnology in animal feeding. This book gives succinct yet comprehensive coverage of products of biotechnology and allied sciences used in animal feed and feeding industries. Particular emphasis is placed on:. - Conservation and upgrading of feeds and feed components. - Increasing the protein value of feeds. - Antimicrobials. - Microbial feed additives. - Increasing the energy value of feeds. Moreover, increasing envi.